2012
DOI: 10.1080/13674676.2012.681482
|View full text |Cite
|
Sign up to set email alerts
|

Biblical literalism among Anglican clergy: what is the role of psychological type?

Abstract: The SIFT method of preaching argues that preachers should attend to the different learning styles implied by psychological type theory when preparing and delivering sermons. The evidence to date that supports the theory behind the method has mainly been based on offering readers of known psychological type a range of interpretations specifically created to appeal to particular type preferences. This paper extends these studies by looking at how a more general interpretative strategy (literalism) is related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
2
12
0
4
Order By: Relevance
“…In general, Biblical views (conservatism -liberalism) were more closely connected with the process of perceiving than with that of evaluating, whereas in the case of dogmatic views it was the other way round. Village (2012) confirmed the existence of a positive relation between a preference for perceiving and literal interpretation of the Bible.…”
Section: Psychological Profile and Religiosity Variablessupporting
confidence: 63%
“…In general, Biblical views (conservatism -liberalism) were more closely connected with the process of perceiving than with that of evaluating, whereas in the case of dogmatic views it was the other way round. Village (2012) confirmed the existence of a positive relation between a preference for perceiving and literal interpretation of the Bible.…”
Section: Psychological Profile and Religiosity Variablessupporting
confidence: 63%
“…The 2013 version included many of the same items, but also some new ones (including those related to beliefs about the Bible), and a measure of (Table 1). It was developed for use within the Church of England and has been shown to have excellent internal reliability in samples of laity and clergy (Village, 2005a(Village, , 2007(Village, , 2012a. The full 12-item scale was presented in the survey and it had an equally high reliability among both laity (α = .90) and clergy (α = .91) in this sample.…”
Section: Samplementioning
confidence: 97%
“…Some studies have drawn on the SIFT method of preaching and hermeneutics (Francis, 2003;Francis & Village, 2008) to show that readers tend to prefer interpretations of Scripture that match their preferred functions in the perceiving or judging processes (Francis, Robbins & Village, 2009;Village, 2010;Village & Francis, 2005). Other studies have shown that literalism is associated with preference for sensing over intuition (Village, 2012a(Village, , 2014. Village (2005aVillage ( , 2007 developed a 12-item scale among Church of England laity to assess the degree of conservative versus liberal belief about the Bible.…”
Section: Bible Beliefs and Psychological Type In The Church Of Englandmentioning
confidence: 99%
See 1 more Smart Citation
“…Ogólnie -poglądy biblijne (konserwatyzm-liberalizm) były bardziej powiązane z procesami postrzegania niĪ z procesami wartoĞciowania, podczas gdy w przypadku przekonaĔ dogmatycznych było dokładnie odwrotnie. Village (2012) potwierdził istnienie pozytywnego związku miĊdzy preferencją percepcji i dosłowną interpretacją Biblii.…”
Section: Ross I Francisunclassified